Endocannabinoid and Cannabinoid-Like Fatty Acid Amide Levels Correlate with Pain-Related Symptoms in Patients with IBS-D and IBS-C: A Pilot Study - Fichna, Jakub; Wood, JodiAnne T.; Papanastasiou, Malvina; Vadivel, Subramanian K.; Oprocha, Piotr; Sałaga, Maciej; Sobczak, Marta; Mokrowiecka, Anna; Cygankiewicz, Adam I.; Zakrzewski, Piotr K.; Małecka-Panas, Ewa; Krajewska, Wanda M.; et al. (PLOS ONE, 2013)
AimsIrritable bowel syndrome (IBS) is a functional gastrointestinal (GI) disorder, associated with alterations of bowel function, abdominal pain and other symptoms related to the GI tract. Recently the endogenous cannabinoid system (ECS) was shown to be involved in the physiological and pathophysiological control of the GI function. The aim of this pilot study was to investigate whether IBS defining symptoms correlate with changes in endocannabinoids or cannabinoid like fatty acid levels in IBS patients. MethodsAEA, 2-AG, OEA and PEA plasma levels were determined in diarrhoea-predominant (IBS-D) and constipation-predominant (IBS-C) patients and were compared to healthy subjects, following the establishment of correlations between biolipid contents and disease symptoms. FAAH mRNA levels were evaluated in colonic biopsies from IBS-D and IBS-C patients and matched controls. ResultsPatients with IBS-D had higher levels of 2AG and lower levels of OEA and PEA. In contrast, patients with IBS-C had higher levels of OEA. Multivariate analysis found that lower PEA levels are associated with cramping abdominal pain. FAAH mRNA levels were lower in patients with IBS-C. ConclusionIBS subtypes and their symptoms show distinct alterations of endocannabinoid and endocannabinoid-like fatty acid levels. These changes may partially result from reduced FAAH expression. The here reported changes support the notion that the ECS is involved in the pathophysiology of IBS and the development of IBS symptoms.